IMPLEMENTASI COLLABORATIVE ONLINE LEARNING UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR MATEMATIKA PADA MATERI RELASI DAN FUNGSI DI SMK NEGERI 9 PANDEGLANG - Tb. Sofwan Hadi; Tb. Ai Munandar (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
This study aims to increase the motivation to learn mathematics of students of class XI SMK Negeri 9 Pandeglang after implementation of Collaborative Online Learning model and to improve student learning result of class XI SMK Negeri 9 Pandeglang after implementation of Collaborative Online Learning model. This study is a classroom action research where the activity takes place in 3 cycles to measure motivation and learning outcomes. Technically after the learning is completed, students are given the task to then the task is sent via email, the activity is done every meeting up to the last cycle. Indicator achievement of learning outcomes exceeds KKM value that is 70 and motivation learn math more than 70% seen from desire and activity study in class. Based on the observation on every activity of learning process progress, result which reached by student is in cycle I viewed from motivation classified as low category that is 30% and average result of learning 64, in cycle II have improvement in motivation that is 70% and in the mean The learning outcome is 68, then on the third cycle student motivation is increasing with the keatifan and students who send the email is all the students and the average learning outcomes achieved is 71